2020
DOI: 10.1007/s10489-020-02029-z
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of a large-scale COVID-19 tweets dataset

Abstract: As of July 17, 2020, more than thirteen million people have been diagnosed with the Novel Coronavirus (COVID-19), and half a million people have already lost their lives due to this infectious disease. The World Health Organization declared the COVID-19 outbreak as a pandemic on March 11, 2020. Since then, social media platforms have experienced an exponential rise in the content related to the pandemic. In the past, Twitter data have been observed to be indispensable in the extraction of situational awareness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 45 publications
0
94
0
5
Order By: Relevance
“…The freely available dataset contained global tweets which were mostly geotagged and filtered using keywords related to COVID-19 such as “ corona ”, “ coronavirus ”, “ coronavirus ” until April 17, 2020. After April 18, 2020, additional filtering keywords including “ covid ”, “ #covid ”, “ covid19 ”, “ covid19 ”, “ covid-19 ”, “ covid-19 ”, “ sarscov2 ”, “ sarscov2 ”, “ sars cov2 ”, “ sars cov 2 ”, “ covid_19 ”, “ covid_19 ”, “ ncov ”, “ ncov2019 ”, “ ncov2019 ”, “ 2019- ncov ”, “ 2019-ncov ”,“ #2019ncov ”, “ 2019ncov ” were added to the tweet dataset [ 29 ]. This freely available tweet data contained only the tweet IDs of the users since the Twitter policy does not provide access to streaming complete tweets and publish to third parties.…”
Section: Methodsmentioning
confidence: 99%
“…The freely available dataset contained global tweets which were mostly geotagged and filtered using keywords related to COVID-19 such as “ corona ”, “ coronavirus ”, “ coronavirus ” until April 17, 2020. After April 18, 2020, additional filtering keywords including “ covid ”, “ #covid ”, “ covid19 ”, “ covid19 ”, “ covid-19 ”, “ covid-19 ”, “ sarscov2 ”, “ sarscov2 ”, “ sars cov2 ”, “ sars cov 2 ”, “ covid_19 ”, “ covid_19 ”, “ ncov ”, “ ncov2019 ”, “ ncov2019 ”, “ 2019- ncov ”, “ 2019-ncov ”,“ #2019ncov ”, “ 2019ncov ” were added to the tweet dataset [ 29 ]. This freely available tweet data contained only the tweet IDs of the users since the Twitter policy does not provide access to streaming complete tweets and publish to third parties.…”
Section: Methodsmentioning
confidence: 99%
“…This work can lead the way for data scientists and frontend engineers to develop up-to-date data modeling and prediction software using Python web frameworks such as Django, 15 Flask, 16 and GUI library such as Tkinter. 17 Also, before our work, one of the largest textual data on Covid-19 was developed by both Google 18 and Johns Hopkins University Centre for Systems Science and Engineering 19 individually. Currently, we can also contribute our sophisticated Twitter data consisting of 600 k tweets with indexed parameters.…”
Section: Discussionmentioning
confidence: 99%
“…They filtered out public sentiment reflection on Covid-19 tweets, as well as visualizing them for a better understanding of the subject matter. Lamsal reported Covid-19 tweet dataset design [ 17 ]. In detail design, the authors have shown people’s understanding during the crisis of the present corona pandemic by temporal and spatial dimension of the dataset.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 twitter datasets were collected from the IEEE Data portal that originated from the LSTM model, developed by Rabindra Lamsal, which monitors the real-time twitter feed for COVID-19-related tweets [11]. It generates over 0.3 million requests every 24 hours and its time-series graph is updated every 30 seconds.…”
Section: Methodsmentioning
confidence: 99%